Establishment of patient-derived orthotopic xenograft model of 1q+ posterior fossa group A ependymoma. Issue 12 (3rd September 2019) - Pierce, Angela M; Witt, Davis A; Donson, Andrew M; Gilani, Ahmed; Sanford, Bridget; Sill, Martin; Van Court, Benjamin; Oweida, Ayman; Prince, Eric W; Steiner, Jenna; Danis, Etienne; Dorris, Kathleen; et al.
Abstract: Background: Treatment for pediatric posterior fossa group A (PFA) ependymoma with gain of chromosome 1q (1q+) has not improved over the past decade owing partially to lack of clinically relevant models. We described the first 2 1q+ PFA cell lines, which have significantly enhanced our understanding of PFA tumor biology and provided a tool to identify specific 1q+ PFA therapies. However, cell lines do not accurately replicate the tumor microenvironment. Our present goal is to establish patient-derived xenograft (PDX) mouse models. Methods: Disaggregated tumors from 2 1q+ PFA patients were injected into the flanks of NSG mice. Flank tumors were then transplanted into the fourth ventricle or lateral ventricle of NSG mice. Characterization of intracranial tumors was performed using imaging, histology, and bioinformatics. Results: MAF-811_XC and MAF-928_XC established intracranially within the fourth ventricle and retained histological, methylomic, and transcriptomic features of primary patient tumors. We tested the feasibility of treating PDX mice with fractionated radiation or chemotherapy. Mice tolerated radiation despite significant tumor burden, and follow-up imaging confirmed radiation can reduce tumor size. Treatment with fluorouracil reduced tumor size but did not appear to prolong survival. Conclusions: MAF-811_XC and MAF-928_XC are novel, authentic, and reliable models for studying 1q+ PFA in vivo. Given the successful response to radiation, these models will be advantageous for testing clinically relevant combination therapies to develop future clinical trials for this high-risk subgroup of pediatric ependymoma.